An adult case of atypical hemolytic uremic syndrome presented with posterior reversible encephalopathy syndrome: Successful response to late-onset eculizumab treatment - Serife Solmaz Medeni (Hematology Reports, 2018)
Atypical hemolytic uremic syndrome is a rare and progressive disease caused by uncontrolled alternative complement activation. Dysregulatıon of the complement activation results in thrombotic microangiopathy and multiorgan damage. A 29-yearold woman who was admitted with complaints of vomiting and headache was detected to have acute renal failure with microangiopathic hemolytic anemia (MAHA). After the diagnosis of atypical hemolytic uremic syndrome (aHUS), she was treated with plasma exchange (PE) and hemodialysis (HD). She has experienced hypertensionrelated posterior reversible encephalopathy syndrome (PRES) at the second plasma exchange. She was initiated on eculizumab therapy because of no response to PE on the 34th days. Her renal functions progressively improved with eculizumab treatment. Dependence on dialysis was over by the 4th month. Dialysis free-serum Creatinine level was 2.2 mg/dL [glomerular filtration rate (e-GFR): 30 mL/min/1.73 m2] after 24 months. Neurological involvement (PRES, etc.) is the most common extrarenal complication and a major cause of mortality and morbidity from aHUS. More importantly, we showed that renal recovery may be obtained following late-onset eculizumab treatment in patient with aHUS after a long dependence on hemodialysis.